THE DEVELOPMENT OF ORAL SPEECH WHEN WORKING WITH A SPECIAL TEXT - Rasulmuxamedova Durdona Tolkundjanovna (American Journals Publishing, 2023)
This article discusses the features of language and speech, as well as the development of oral and written speech of students through working with text. The article presents tasks and examples that encourage students to understand the grammar of the Uzbek language by working with texts orally and in writing, as well as aspects that should be paid attention to when compiling them.
Keywords: language, discourse, text, oral and written speech, communication, specialty, jurisprudence and legal terms.